Marija Gimbutas 100: A ‘Grande Dame’ of Twentieth-Century Prehistory and Her Connections with Hungarian Archaeology - Bánffy, Eszter (Historical Studies on Central Europe, 2022)
Prehistoric archaeologist and cultural anthropologist Marija Gimbutas was born exactly a century ago. Although she left us over a quarter of a century ago (she passed away in 1994), her person and her still controversial ideas continue to attract considerable interest, reflected both by the acclaim and the harsh critique that her work and theories have received and continue to receive. In light of recent archaeogenetic findings and their interpretation, the debate has even intensified over the past few years.